3x-7(-2x-13)=3(-2x+9)

Simple and best practice solution for 3x-7(-2x-13)=3(-2x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-7(-2x-13)=3(-2x+9) equation:


Simplifying
3x + -7(-2x + -13) = 3(-2x + 9)

Reorder the terms:
3x + -7(-13 + -2x) = 3(-2x + 9)
3x + (-13 * -7 + -2x * -7) = 3(-2x + 9)
3x + (91 + 14x) = 3(-2x + 9)

Reorder the terms:
91 + 3x + 14x = 3(-2x + 9)

Combine like terms: 3x + 14x = 17x
91 + 17x = 3(-2x + 9)

Reorder the terms:
91 + 17x = 3(9 + -2x)
91 + 17x = (9 * 3 + -2x * 3)
91 + 17x = (27 + -6x)

Solving
91 + 17x = 27 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
91 + 17x + 6x = 27 + -6x + 6x

Combine like terms: 17x + 6x = 23x
91 + 23x = 27 + -6x + 6x

Combine like terms: -6x + 6x = 0
91 + 23x = 27 + 0
91 + 23x = 27

Add '-91' to each side of the equation.
91 + -91 + 23x = 27 + -91

Combine like terms: 91 + -91 = 0
0 + 23x = 27 + -91
23x = 27 + -91

Combine like terms: 27 + -91 = -64
23x = -64

Divide each side by '23'.
x = -2.782608696

Simplifying
x = -2.782608696

See similar equations:

| 500+2x=10000-4x | | -1/4=2/3x-2/5 | | 1/4=4 | | 6t+5=t+25 | | 15x=2/3 | | -14=2x | | 3x-20=15-2x | | 3+5x-4-7x=-4x+1 | | 3b^20/3a^14 | | 9x+x+9x+x-30=370 | | 8x-2=-9+5x+2 | | 2(6.5+l)=34 | | 7/41.4 | | -1+5x+7=-24 | | -5/6(=2x)=40 | | 4n+4=4 | | a/5-5/6=a/3 | | 8=8+7b+5b | | -3w+w^2=6 | | 3x-10=14-x | | h=at-0.25 | | 6n+5-5=0 | | z^2+4z+18=0 | | 14x-13x=15 | | F*12=204 | | 5=4-8r-7 | | 18x-16x-2=18 | | 1x^2+4x+18=0 | | 20x-8x-11x-1=15 | | -13+2x=12-3x | | 3x-3x+4x+x=5 | | 5x+2x-3x+4x+x=18 |

Equations solver categories